Geometric edge barrier in the Shubnikov phase of type II superconductors: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Brandt, Ernst Helmut (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
In type II superconductors the magnetic response can be irreversible due to two different reasons: vortex pinning and barriers for flux penetration. Even without bulk pinning and in absence of a microscopic Bean-Livingston surface barrier for vortex penetration, superconductors of nonellipsoidalshape can exhibit a large geometric barrier for flux penetration. This edge barrier and the resulting irreversible magnetization loops and flux-density profiles are computed from continuum electrodynamicsfor superconductor strips and disks with constant thickness, both without and with bulk pinning. Expressions are given for the field of first flux entry Hen and for the reversibility field Hrev above which the pin-free magnetization becomes reversible. Both fields are proportional to the lower critical field Hc1 but else depend only on the specimen shape. These results for rectangular cross section are compared with the well known reversible magnetic behavior of ideal ellipsoids.